3D petroleum secondary migration modeling of the Jurassic petroleum system in part of the West Siberia basin; Book of Abstracts of the Communications presented to the 22nd International Meeing on Organic Geochemistry, Seville - Spain, September 12-16, 2005; Vol. 1 - Goncharov I. V. Ivan Vasilyevich; Romanov A. G.; Gagarin A. N.; Carruthers D. J.; Corbett P. W. M.; Afanasenkov A. P. (2005, 2005)
В фонде НТБ ТПУ отсутствует